Echowall (Project Echowall, 2020)
"[...] a collaborative research platform based at the University of Heidelberg’s Institute of Chinese Studies that draws on the expertise of a broad spectrum of experts in both Europe and China to gain a clearer picture of the China-Europe relationship in all dimensions [...]"
Gesehen am 06.02.2020
Keywords: Website